The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/gps.2384
|View full text |Cite
|
Sign up to set email alerts
|

A review comparing the safety and tolerability of memantine with the acetylcholinesterase inhibitors

Abstract: Objective: Alzheimer's disease (AD) is prevalent among elderly people, who often have comorbid conditions, and may be prescribed multiple medications. Drug safety and tolerability is paramount in maximising efficacy and optimising patient and carer quality of life, as patients are vulnerable to adverse events (AEs) and/or compliance difficulties. The two principal categories of drug used in the treatment of AD are the acetylcholinesterase inhibitors (AChEIs) and the NMDA-receptor antagonist, memantine. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 18 publications
(31 reference statements)
2
56
0
3
Order By: Relevance
“…Its pharmacological profile is well known and has been extensively described [8][9][10][11][12][13][14][15][16] .…”
Section: Memantinementioning
confidence: 99%
“…Its pharmacological profile is well known and has been extensively described [8][9][10][11][12][13][14][15][16] .…”
Section: Memantinementioning
confidence: 99%
“…A recent review (Jones, 2010) of the most recent safety/tolerability data for memantine (derived from meta-analyses, pooled analyses, European SPCs, and EMEA publications) confirmed that memantine has a favorable tolerability profile when used in monotherapy or in combination with other agents. Moreover, results of studies of a total treatment period of up to two years show that memantine is safe and tolerated, with an adverse event profile almost indistinguable from that of placebo.…”
Section: Post-marketing Datamentioning
confidence: 99%
“…Although its actual efficacy on the AD patient's quality of life has proven to be moderate (Emre et al, 2008;Kaduszkiewicz & Hoffmann, 2008), several pre-marketing and postmarketing studies have demonstrated the excellent safety and tolerability profile of the drug (Farlow & Phillips, 2008;Jones, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Anticonvulsants have been shown to be of limited efficacy both as a monotherapy and in combination with lithium [1,[3][4][5][6][7] and the mood stabilizing effect of atypical antipsychotics has been severely questioned [8,9]. Thus, the research and development of more effective moodstabilizers for the prophylaxis of bipolar patients resistant to lithium, is an urgent challenge of modern psychopharmacology.Indeed, even with currently available treatments, patients with BD remain unwell in 50% of their time, with about 75% of this time spent in depression [6].We have recently suggested that blockade of NMDA receptors by memantine, a drug with excellent safety and tolerability profile [10], could result in an antimanic and mood-stabilizing effect in treatmentresistant BD patients [11,12].Our group found suggestive evidence of the mood-stabilizing effect of memantine when added to stable, ongoing but inadequately effective standard treatments in 40 BD patients in two 6 and 12-month clinical trials [13,14].Memantine as a monotherapy also has been reported to show beneficial effects in few individual BD patients, including after discontinuation of lithium treatment [15][16][17][18].Finally, we reported the results of a three-year naturalistic study of adding memantine to 30 treatment-resistant bipolar patients [19]. In this trial, memantine achieves clinically meaningful long-term benefits, for both depressive and mania-like (mania, hypomania) morbidity, in outpatients who had proved resistant to standard treatments for more than 3 years, until memantine (20-30 mg/day) was added to otherwise stable regimens for another 3 years, during which patients improved progressively.…”
mentioning
confidence: 99%
“…We have recently suggested that blockade of NMDA receptors by memantine, a drug with excellent safety and tolerability profile [10], could result in an antimanic and mood-stabilizing effect in treatmentresistant BD patients [11,12].…”
mentioning
confidence: 99%